Risk Factors of Preeclampsia in Raden Mattaher Hospital, Jambi - Devi Natalia; Listyaning Eko Martanti; Budi Astyandini (JURNAL KEBIDANAN, 2022)
Preeclampsia is the major cause of maternal-neonatal death, with an estimated incidence 2-8% of pregnancies. The purpose of this study was to determine risk factors that most influence the incidence of preeclampsia in pregnant women in Jambi province. This study used an analytic observational method with a case-control study design. By using purposive sampling, 125 pregnant women with preeclampsia were found as a case group at Raden Mattaher Hospital and 125 normal pregnant women as a control group at Lambur Health Center. The results showed there was a significant difference between age (p-value 0.002), parity (p-value 0.073), gestational interval (p-value 0.0001), hypertension history (p-value 0.0001), Multiple Pregnancy (p-value 0.366), BMI (p-value 0.0001 ) and hemoglobin levels (p-value 0.003) with incidence of preeclampsia. Then multiple  logistic regression analysis showed  that hemoglobin level (OR 23.5/CI 3.5-157.3), hypertension history (OR 13.2/CI 4.4- 39.5) and BMI (OR1 6.1 CI 2.5-15.3/ OR2 5.0 CI 2.1-12.0) are the  most dominant risk  factor  that  causes  preeclampsia. The conclusion there are relationship between age, gestational age, hypertension history, BMI and hemoglobin levels with the incidence of preeclampsia